Motivasi Siswa Putra dalam Mengikuti Ekstrakurikuler Sepak Bola di SMP Negeri 1 Seberuang Kabupaten Kapuas Hulu - kurniawan, antonius (Journal Sport Academy, 2024)
The purpose of this study was to determine the intrinsic and extrinsic motivational factors of students in participating in soccer extracurricular activities at State Junior High School 1 Seberuang, Kapuas Hulu Regency. This study employed a single variable, namely “student motivation”, using a quantitative descriptive method in the form of a survey, with a questionnaire as the primary data collection instrument. The data collection techniques used in this study were the indirect communication technique and the documentary study technique, since the researcher employed a questionnaire as an intermediary for the respondents. The questionnaire data on student motivation were processed using statistical formulas through descriptive analysis with percentages. Based on the data analysis, the motivational level of male students in participating in soccer extracurricular activities at State Junior High School 1 Seberuang, Kapuas Hulu Regency was found to be in the moderate category, with 47% or 14 out of 30 students.